REVIEW PAPERThe genetics of melanoma - Brudnik, Urszula; Wojas-Pelc, Anna; Branicki, Wojciech (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2006)
Melanoma is an important public health issue and research strategies are trying to elucidate the relative contribution of genes and environmental factors in its causation. In terms of genetic factors the discovery of cell cycle genes – CDKN2a, CDK4 – has been a great advance. Current studies aim to identify other susceptibility genes and to determine the interactions of the various genetic and environmental factors. Among them, MC1R (Melanocortin-1 receptor gene), PTEN, BRAF, NRAS are being analysed more closely. Epistatic (gene-gene) and gene environmental interactions studies aim to recognize individuals at high risk.